2013
DOI: 10.3390/s130303941
|View full text |Cite
|
Sign up to set email alerts
|

Simple Fabrication Process for 2D ZnO Nanowalls and Their Potential Application as a Methane Sensor

Abstract: Two-dimensional (2D) ZnO nanowalls were prepared on a glass substrate by a low-temperature thermal evaporation method, in which the fabrication process did not use a metal catalyst or the pre-deposition of a ZnO seed layer on the substrate. The nanowalls were characterized for their surface morphology, and the structural and optical properties were investigated using scanning electron microscopy (SEM), X-ray diffraction (XRD), transmission electron microscopy (TEM), and photoluminescence (PL). The fabricated Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 24 publications
1
22
0
2
Order By: Relevance
“…Among them, many different nanostructures of ZnO such as nanowires, nanorods, nanoparticles, and nanofibers have been proposed as high-performance relative humidity (RH) sensors [93][94][95][96]. Following the increased interest in the Chen et al, in two different papers [90,91], investigated the hydrogen-and methane-sensing performance of 2D ZnO nanowalls. they were directly grown on a glass substrate by thermal evaporation of zinc powder at 450 • C. The fabrication process did not use a metal catalyst or the pre-deposition of a ZnO seed layer on the substrate.…”
Section: Humiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, many different nanostructures of ZnO such as nanowires, nanorods, nanoparticles, and nanofibers have been proposed as high-performance relative humidity (RH) sensors [93][94][95][96]. Following the increased interest in the Chen et al, in two different papers [90,91], investigated the hydrogen-and methane-sensing performance of 2D ZnO nanowalls. they were directly grown on a glass substrate by thermal evaporation of zinc powder at 450 • C. The fabrication process did not use a metal catalyst or the pre-deposition of a ZnO seed layer on the substrate.…”
Section: Humiditymentioning
confidence: 99%
“…In addition, the better selectivity compared to other species was attributed to the ability of H 2 S to form a metal sulfide on the surface of metal oxides, which leads to a large variation in the resistance. Chen et al, in two different papers [90,91], investigated the hydrogen-and methane-sensing performance of 2D ZnO nanowalls. They were directly grown on a glass substrate by thermal evaporation of zinc powder at 450 °C.…”
Section: Other Gasesmentioning
confidence: 99%
“…Pure and doped ZnO films prepared by different methods were found to be sensitive to H 2 S gas. [16][17][18][19][20] ZnO-based gas sensors were also found to be suitable for detection of gases like methane, 21,22 formaldehyde, 23-25 ethanol, [26][27][28][29] ammonia, 30-34 LPG, [35][36][37] methanol, 38 propanol, 38,39 and NO 2 . 18,[40][41][42][43][44] In the present context we report the NO 2 and H 2 S gas sensing characteristics of oxygen-deficient nanocrystalline zinc oxide films prepared by chemical spray pyrolysis (CSP) technique on glass substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The fabricated sensor showed good sensing properties towards NO 2 monitoring at room temperature. Chang et al showed excellent sensing behavior towards different gases, including CO, hydrogen and methane, of two-dimensional ZnO nanowalls grown on glass substrate by thermal evaporation at low temperature without any catalysts or the pre-deposition of a ZnO seed layer on the substrate [12][13][14].…”
Section: Introductionmentioning
confidence: 99%